Marshall's evolutionary economics - Raffaelli, Tiziano, 1950- (Routledge studies in the history of economics, 2003)
Alfred Marshall was one of the most important economists ever to have lived. This excellent new book suggests that Marshall anticipated some of the views that are now associated with the cognitive sciences.